Exploring Doctors' Willingness of Providing Service on COVID 19: A Case Study in Bangladesh - Sayeda Kamrunnahar Bristy; Kamrul Hasan; Muhammad Ariful Haque; Umme Habiba (Journal of Epidemiology and Public Health, 2021)
Background: Doctors were doing the hardest to deal with COVID-19 emergency medication deliberately when Bangladesh experienced doctors' shortage along with a high mortality rate for